Eating Behaviour and Body Mass Index in Children with Attention-Deficit Hyperactivity Disorder - Dr Tafheem Kanwar; Dr. Tamanna Hooda; Dr Pooja Bhatia, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: ADHD has been associated with impaired reward processing and self-regulation that can incline the patient to distorted meals and a weighty excess. Data indicate a greater body mass index (BMI) and obesogenic eating in Indian children regarding ADHD, but limited data are available regarding Indian children. We analysed the relationship between eating behaviours and BMI between offspring with ADHD and normally developing peers. Methods: In a case control study at a Child and Adolescent Guidance Clinic (April 2021 July 2022), 30 drug naive children with ADHD (DSM-5; age 611 years) and 30 age, sex and income matched controls were recruited. They were asked to give their ADHD assessment using Vanderbilt ADHD Parent Rating Scale, the Conner index Parent 10-item Conner and Child Eating behavior Questionnaire (CEBQ). The same standard procedures were used to measure height and weight; BMI was determined (kg/m 2). Comparisons between groups were done using t test/WilcoxonMann Whitney test, Chi-square/Fisher exact test; correlations, using Spearman rho test (PSPP v23; -0.05). Results: Mean age did not differ (ADHD 8.17±2.21 vs controls 8.16±2.17 years; p=0.870); 83.3% were male. Mean BMI was higher in ADHD (17.02 vs 14.68 kg/m²; Wilcoxon W=610.5, p=0.018). Weight categories differed (underweight 16.7% vs 40.0%; overweight 23.3% vs 6.7%; obese 16.7% vs 3.3%; Fisher’s exact p=0.039). On CEBQ, enjoyment of food (83.3% vs 60.0%; χ²=4.022, p=0.045) and food responsiveness (70.0% vs 43.3%; χ²=4.344, p=0.037) were more frequent in ADHD. Emotional under-eating scores were lower in ADHD (11.93±3.55 vs 14.10±3.97; p=0.030). A moderate, statistically significant correlation was observed between ADHD severity (Conner’s score) and emotional overeating (r=0.32). No significant associations were found between eating behaviours and age, sex, family income, or neighbourhood. Conclusion: Indian children with ADHD show higher BMI and greater prevalence of overweight/obesity than controls, accompanied by increased food responsiveness and enjoyment of food. Emotional overeating correlates with ADHD symptom severity. Routine screening for eating behaviours and weight status should be integrated into ADHD care, with early behavioral and nutritional interventions. Larger, community-based longitudinal studies are warranted.